2021
DOI: 10.3390/nu13103512
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Diet Quality: A Cross-Sectional Study of 1055 University Students

Abstract: Given that there is only a limited body of evidence available concerning the dietary habits of Spanish university students, the present study assesses the quality of this group’s diet, their adherence to the National Food-Based Dietary Guidelines, and the predictive factors of their diet quality. To do so, a cross-sectional study was performed on a sample of 1055 students. The quality of the participants’ diets was then analysed by using the Spanish Healthy Eating Index, and then their level of compliance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 90 publications
(91 reference statements)
3
21
1
1
Order By: Relevance
“…They often cut down or skip meals, prefer to eat fast food, snack between meals, and consume alcohol regularly [4]. University students typically follow a diet that is high in fat and low in dietary fibre [4], with low consumption of fruits and vegetables, which is contrary to the principles of a Mediterranean diet (MD) [5]. The university stage is important for the development of eating habits and future health [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They often cut down or skip meals, prefer to eat fast food, snack between meals, and consume alcohol regularly [4]. University students typically follow a diet that is high in fat and low in dietary fibre [4], with low consumption of fruits and vegetables, which is contrary to the principles of a Mediterranean diet (MD) [5]. The university stage is important for the development of eating habits and future health [4].…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, the majority of people follow a Mediterranean diet, which is a healthy diet [7]. Previous research has revealed that the low adherence of Spanish university students to a Mediterranean diet is related to high alcohol consumption [5,8], smoking, low levels of physical activity (PA), living alone, and leading a sedentary lifestyle [5], and good adherence to the Mediterranean diet is associated with an improved quality of life related to perceived health [9] and low body weight [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the same line, Xiao et al [ 42 ] demonstrated that the timing of carbohydrate and protein was related with obesity. Last but not least, chronotype can be influenced by social, cultural, and economic factors [ 43 ]. The Mediterranean diet, characterized by high intake of fruit, vegetables, legumes, cereals, and using olive oil as the main lipid, is considered a healthy diet [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transition to university in young adults involves a greater autonomy concerning food choices, low food budget, and exposure to new social groups than usual [ 5 , 6 ]. Indeed, the transition from living at home with parents to autonomous university life is often associated with changes such as an increase in alcohol and sugar intake while at the same time a decrease in the consumption of fruits and vegetables [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%